The Spreading of Innovation: State Adoptions of Energy and Climate Change Policy. Issue 5 (September 2016) - Bromley‐Trujillo, Rebecca; Butler, J. S.; Poe, John; Davis, Whitney
Abstract: The American states are engaged in a variety of policy efforts to mitigate climate change and alter energy usage. While a number of studies have considered the reasons for adoption of renewable energy and climate change policies, they typically consider only one policy in isolation. This study examines policy adoption of 14 energy and climate change programs in a pooled event history analysis. Our primary research questions consider average effects of horizontal policy diffusion, while also identifying factors that vary across policy type. We offer a method of testing whether predictors vary across policies and use this test to incorporate interactions by policy in the statistical analysis. Our results indicate that many of the primary drivers of adoption are political in nature, including state ideology, environmental interest group membership, and diffusion via ideologically similar neighbors. In addition, we find that given policy heterogeneity, a number of determinants vary by policy type, though differences are in magnitude rather than direction.